Cosmeticeutical products from antimicrobial active extracts of the stem barks of Entada spiralis Ridl.(Akar Sintok) - Mat So'ad, Siti Zaiton; Harun, Aiza; Mohd Hassan, Norazian; Abdullah, Jariah (2012)
Entada spiralis, locally known as “beluru” or “sintok” is a perennial non-climbing shrub. It grows wildly especially in the tropical rain forest such as Malaysia, Thailand and Indonesia. Bioassay guided-isolation of methanolic extract from the stem barks revealed that medium polar fraction of the extract contained a few compounds that inhibit the growth of dermatophytes skin caused diseases. Minimum inhibitory concentration of the fraction gave a significance antidermatophytic effect on selected dermatophytes which are Trichophyton rubrum, Trichophyton mentagrophytes and Microsporum gypseum. This finding gives scientific evidence for the traditional uses of the stem barks of E. spiralis by the Malays, as soap, shampoo and scrub in treating skin problems. So far, we have discovered that methanolic crude extract and fraction have potential to be commercialized as skin care products. A series of skin care products has been formulated from the stem barks, that gave a very good testimony results from most of the clients or users, especially the soap and hair tonic.Thus, a very good signs for us to further our study on standardization of the active fraction, as requirement for herbal products to be accepted by registered authorities